Overview of Medication Adherence in Patients with Diabetes Mellitus - heryanto, tri; Sinaga, Labora; Sinaga, Tiurmawati; Huda, Khairul; Soeta bangsa, Yudha Fatih; Aniroh, Umi (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Medication adherence is an important factor in the successful management of diabetes mellitus. Poor adherence to medication therapy may lead to suboptimal blood glucose control and increase the risk of complications. This study aimed to describe medication adherence among diabetes mellitus patients at Puskesmas Permata Kecubung, Puskesmas Melata, and Sultan Imanuddin Hospital. This study used a descriptive quantitative design with a cross-sectional approach. A total of 116 respondents were selected using purposive sampling. Data were collected over four days starting from April 12, 2026 using a medication adherence questionnaire. Data were analyzed using univariate analysis in the form of frequency distribution and percentage. The results showed that most respondents were in the adherent category (54 respondents; 46.6%), followed by moderately adherent (39 respondents; 33.6%), and non-adherent (23 respondents; 19.8%). In conclusion, medication adherence among diabetes mellitus patients in the three study sites was generally in the adherent category, although some patients were still non-adherent. Therefore, health education and treatment monitoring by healthcare workers need to be improved.